Device-mediated customer behaviour on the internet: A systematic literature review - Lukas Wolf (International Journal of Consumer Studies, 2023)
The proliferation of smartphones, tablets and other digital devices in addition to traditional computers has transformed the Internet into a device-mediated environment. While these devices provide immediate access to similar Internet sources, they differ significantly in their characteristics, such as screen size, operation mode and context of use. As a consequence, behaviours on the Internet along the customer journey vary substantially depending on the device used. To summarize the fast-growing body of research on device-mediated customer behaviour, a systematic, framework-based literature review of 59 articles from the last decade was conducted. Through an examination of the antecedents, decisions and outcomes investigated in the publications, the review presents a conceptual framework that highlights the relation between device characteristics, decision processes and behavioural outcomes. The review further summarizes the theories, contexts and methods employed in the studies and sets an extensive future research agenda. We found that the extant literature lacks comprehensive theories and clear definitions of digital devices in the omnichannel environment. Furthermore, existing findings should be generalized for other contexts (e.g. industries and countries) and validated via the introduction of other research designs and methods. The understanding of device-mediated behaviour and the consequently arising marketing measures remains scarce. Thus, this review advances the comprehension of customer behaviour on the Internet and provides researchers and practitioners with information on the implications for customer experience and omnichannel management.
Keywords: 330; customer behaviour; customer experience management; digital devices; omnichannel management; systematic literature review; TCM-ADO framework